2021
DOI: 10.1007/s00264-021-04940-7
|View full text |Cite
|
Sign up to set email alerts
|

The safety of outpatient total shoulder arthroplasty: a systematic review and meta-analysis

Abstract: Purpose To meet the increasing demands of total shoulder arthroplasty (TSA) while reducing its financial burden, there has been a shift toward outpatient surgery. This systematic review and meta-analysis aimed to evaluate the safety of outpatient TSA. Methods The primary objective was to compare re-admission rates and postoperative complications in outpatient versus inpatient TSA. The secondary objectives were functional outcomes and costs. PubMed, Google … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Our findings are consistent with several other studies supporting the safety of outpatient aTSA. In a systematic review and meta-analysis of outcomes of inpatient and outpatient aTSA, Ahmed et al 1 found no significant differences across all complications between groups, which remained consistent when analyzing database 6 , 7 , 13 , 22 , 24 , 28 and nondatabase 12 , 17 , 27 studies as part of a subgroup analysis. Although these studies were unable to find a significant difference across all complications, the present study detected a significantly lower rate of severe adverse events in the outpatient cohort.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our findings are consistent with several other studies supporting the safety of outpatient aTSA. In a systematic review and meta-analysis of outcomes of inpatient and outpatient aTSA, Ahmed et al 1 found no significant differences across all complications between groups, which remained consistent when analyzing database 6 , 7 , 13 , 22 , 24 , 28 and nondatabase 12 , 17 , 27 studies as part of a subgroup analysis. Although these studies were unable to find a significant difference across all complications, the present study detected a significantly lower rate of severe adverse events in the outpatient cohort.…”
Section: Discussionmentioning
confidence: 81%
“…Several institutional studies comparing outpatient and inpatient aTSA procedures have reported similar complication and readmission rates between groups, supporting the notion that outpatient aTSA procedures can be safe and cost-saving in appropriately selected patients. 1 , 5 , 7 , 10 , 12 , 14 , 17 , 24 , 27 , 38 For example, in single-surgeon centers, Borakati et al 10 and Brolin et al 12 found similar rates of total complications for inpatient and outpatient aTSA procedures. However, these studies may have been underpowered to detect a difference in outcomes and limited to specialized academic centers.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“… 7 , 10 , 18 Indeed, a recent meta-analysis found no significant differences between matched inpatient and outpatient TSA groups in regard to medical complications, surgical complications, or hospital readmissions. 1 Compared with the aforementioned database studies, the present study benefits from the addition of more recent ACS-NSQIP data to include a greater number of outpatient procedures. We were also able to observe trends over time by dividing patients between an early and late cohort.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 26 These developments have spurred interest in performing TSA in the outpatient setting, which has been shown to be safe and effective. 1 Approximately 2%-3% of TSA procedures were performed outpatient in the early 2010s, and that proportion has steadily increased, with the number of TSAs performed in ambulatory surgery centers doubling over a 5-year span. 3 , 9 , 23 Leroux et al found high levels of patient satisfaction with outpatient TSA, as 97% of patients described their experience as good or excellent, and over 94% said they would choose outpatient TSA again.…”
mentioning
confidence: 99%